Boy : tales of childhood - Dahl, Roald; Blake, Quentin (India: Puffin, 2013)
A young English boy describes his relationship with his father and the special adventure they share together.
Keywords: v; Authors, English -- 20th century -- Biography -- Juvenile literature; Dahl, Roald